A phylogenomic perspective reveals mitochondrial-nuclear discordance and previously undescribed species nested within a widespread East African Reed frog species (Hyperolius substriatus Ahl, 1931) - Lucinda P. Lawson; Gabriela B. Bittencourt-Silva; Werner Conradie; Daniel M. Portik; Simon P. Loader (PLoS ONE, 2025)
The sub-montane East African Reed Frog, Hyperolius substriatus Ahl, 1931 (Spotted Reed Frog) has a fragmented highland distribution throughout East Africa. Previous studies show extensive mitochondrial divergence between four lineages of African Spotted Reed Frogs that roughly correspond to previously-recognized subspecies. These may have conservation implications if formally described. However, as mitochondrial-based population models only track maternal patterns, further genomic datasets are necessary to assess the distinctness of these lineages in relation to historically recognized morphological subspecies. In this study, we expanded sampling to newly discovered localities and assessed mitochondrial and genomic data to better understand phylogeography and landscape genomics of this species. We found that genomic clades (biparentally inherited) confirm some of the mitochondrial structure (female inherited), but also revealed multiple cases of mitonuclear discordance particularly within the Udzungwa Mountain block, which may have two separate founding events based on peripatric mitochondrial lineages and panmictic genomic signals. Taken together, the three clades within the geographical range of H. substriatus through Tanzania, Malawi, and Mozambique correspond to three previously-identified subspecies and lineages, and have both spatially cohesive and population-specific patterns of geneflow and isolation with neighboring highland locations.